Endocrinology : adult & pediatric - Jameson, J. Larry; DeGroot, Leslie J.; De Kretser, D. M.; Giudice, Linda; Grossman, Ashley; Melmed, Shlomo; Potts, John T., 1932-; Weir, Gordon C. (Elsevier/Saunders, 2016)
Considered the definitive source in its field for over 35 years, Endocrinology: Adult and Pediatric, has been thoroughly updated to reflect today's recent advances in adult and pediatric endocrinology. Unique perspectives from a team of trusted, world-renowned experts ensure this medical reference book remains the most highly-regarded text in the field.- Resumé vydavatele
Keywords: endokrinologie; endokrinní žlázy; nemoci endokrinních žláz; endocrinology; endocrine glands; endocrine gland diseases; elektronické knihy; učebnice; electronic books; textbooks